Cancer stem cells: controversies in multiple myeloma - Brennan, Sarah K. (2009)
Increasing data suggest that the initiation, relapse, and progression of human cancers are driven by specific cell populations within an individual tumor. However, inconsistencies have emerged in precisely defining phenotypic markers that can reliably identify these “cancer stem cells” in nearly every human malignancy studied to date. Multiple myeloma, one of the first tumors postulated to be driven by a rare population of cancer stem cells, is no exception. Similar to other diseases, controversy surrounds the exact phenotype and biology of multiple myeloma cells with the capacity for clonogenic growth. Here, we review the studies that have led to these controversies and discuss potential reasons for these disparate findings. Moreover, we speculate how these inconsistencies may be resolved through studies by integrating advancements in both myeloma and stem cell biology.